"Act-as-if you are infected and infectious": what has the global therapeutic community movement learnt from COVID-19?. Issue 3 (26th November 2020) - Gosling, Helena; Yates, Rowdy
Abstract : Purpose: The purpose of this paper is twofold: to reflect upon what the global therapeutic community (TC) movement has learnt from coronavirus and to consider how TCs will continue to adapt and evolve in a post-pandemic climate. Design/methodology/approach: This is a viewpoint paper based on the authors' participation in an international learning event whereby speakers from TCs from around the world spoke about how they adapted their services to overcome adversity. Findings: The findings are usefully thought out as shelter, creativity, reintegration and employment, technology and roots. Based on the material discussed in the learning event, it would seem that the global TC movement has engaged in a process of looking to the past to move forward by drawing upon founding principles and prescriptions of the TC tradition, rooted in humanistic and indeed humanitarian responses to staff, client and sociocultural needs. Originality/value: According to the author, this paper is one of the first attempts to capture how TCs from across the globe have responded to the threat of coronavirus.